Remodelling of sinus bone grafts according to the distance from the native bone: A histomorphometric analysis - Pignaton, Tulio Bonna [UNESP]; Spin-Neto, Rubens; Ferreira, Carlos Eduardo de Almeida; Martinelli, Carolina Borges; de Oliveira, Guilherme José Pimentel Lopes; Marcantonio Jr, Elcio [UNESP] (Wiley, 2020)
Objectives: To evaluate graft remodelling according to the distance from the native bone in maxillary sinuses grafted with anorganic bovine bone (ABB). Material and methods: Bilateral sinus grafting was performed in twenty patients with residual bone height <5 mm before implant placement. After 8 months, biopsy samples were harvested, and histomorphometric analysis was performed to examine bone formation according to the distance (in mm) from the native bone (sinus floor). In the grafted area, the percentages of new bone (NB), residual graft material (rABB), and soft tissue (ST) were evaluated. Results: A total of 103 biopsy samples were evaluated, and the percentages of NB, rABB, and ST were 31.62 ± 9.85%, 18.94 ± 7.88%, and 49.41 ± 9.52%, respectively, in the 1st mm; 27.15 ± 9.83%, 23.33 ± 9.45%, and 49.53 ± 11.73%, respectively, in the 2nd mm; 23.61 ± 13.02%, 21.35 ± 11.08%, and 55.03 ± 16.14%, respectively, in the 3rd mm; and 21.67 ± 12.29%, 19.67 ± 10.28%, and 58.66 ± 12.46%, respectively, in the 4th mm. The 1st millimetre of the grafted area (closer to the native bone) presented a larger amount of NB than the other portions of the grafted areas and a smaller amount of rABB than the 2nd mm of the grafted area (p <.05). The amount of ST was larger in the 3rd and 4th mm of the grafted area than in the first 2 millimetres (p <.05). Conclusion: The distance from the native bone influences bone formation following maxillary sinus augmentation.
Keywords: bone formation; bone substitutes; clinical trial; sinus augmentation